Uji Karbon Teraktivasi H2SO4 Hasil Pirolisis Untuk Adsorbsi Ion Logam Kromium (Cr) - Andrian Adhi Susila; Safaah Nurfaizin; Laeli Kurniasari; Sufrotun Khasanah (Fakultas Teknik dan Rekayasa, 2025)
Heavy metal pollution such as chromium (Cr) in industrial wastewater is a serious environmental problem because of its impact on human health and aquatic ecosystems. One effective method to reduce Cr levels in waste is adsorption using activated carbon based on natural materials. This study aims to examine the effectiveness of activated carbon obtained from pyrolysis wood twig waste in absorbing Cr ions. Activated carbon was activated using sulfuric acid (H₂SO₄) with concentration variations of 1, 3, and 5 M to increase adsorption capacity. Adsorption tests were carried out with contact time variations of 60, 90, and 120 minutes, and analyzed using Atomic Absorption Spectroscopy (AAS). The results showed that activated carbon with H₂SO₄ activation increased adsorption capacity against Cr ions. The higher the concentration of H₂SO₄, the lower the water content and ash content in activated carbon, which indicates an increase in surface area and porosity. The effect of initial Cr concentration on adsorption effectiveness was also observed. At an initial concentration of Cr of 10 ppm, activated carbon was able to absorb up to 58.73% of the total metal ions present. However, when the initial concentration was increased to 25 ppm, the adsorption effectiveness decreased to 41.28%. At a higher concentration, namely 50 ppm, activated carbon was only able to absorb 34.78% of Cr ions. These results indicate that activated carbon from pyrolysis wood twig waste can be an economical and environmentally friendly alternative for the treatment of waste containing heavy metals.